THE “STEEL BOND” BETWEEN SOUTH KOREA AND NATO: TRACING THE CHRONOLOGY AND DEEPENING OF COOPERATION SINCE 2022 - Simikić , Siniša (Politeia, 2026)
This paper describes and explains the relationship and cooperation between South Korea and NATO from the establishment of their relations to 2025. It analyzes the drivers of cooperation and traces its development during the first decades of the 21st century, with particular emphasis on the historical factors that led to the emergence of this cooperation. In addition, the paper examines NATO’s policy toward the Indo-Pacific region and South Korea’s position within this process. Special attention is devoted to the deepening of cooperation between NATO and South Korea following the outbreak of the conflict in Ukraine in 2022. The intensification of cooperation is reflected in multiple dimensions, ranging from the strengthening of formal ties to increased procurement of weapons and military equipment by NATO member states from South Korea. The paper also analyzes respective positions toward North Korea and the impact of North Korea on the strengthening of NATO–South Korea cooperation. The paper’s central thesis is that NATO–South Korea cooperation is evolving from a largely symbolic partnership into a substantive and intensive collaboration, driven by NATO’s need to expand its presence in the Indo-Pacific, South Korea’s pursuit of a reliable security partner, and its goal to strengthen defense-industrial ties with NATO member states. The paper employs comparative and analytical methods.
Keywords: South Korea; NATO; “Steel Bond”; Cooperation; United States; Armament